304 Pathology-Directed Perioperative Tracking System for Patient Safety and Quality Assurance. (11th January 2018) - Coldren, Daniel; Kertowidjojo, Elizabeth
Abstract: In the practice of surgical pathology, cooperation between the surgical team and the pathology team can be riddled with many challenges. Communication is often the root of many concerns, as time constraints make constant dialogue between the surgeon and pathologist unfeasible. To resolve this problem, we have developed an electronic pathology-directed perioperative tracking system (PD-PTS) as a way for pathologists to monitor scheduled, ongoing, and completed procedures. Previously, a perioperative tracking system (PTS) through Cerner SurgiNet was available to the pathologist. This system, however, is tailored for the use of surgeons and incorporates information that does not pertain to the practice of pathology, such as the completion of procedural consent, obtainment of patient's history, and the level of surgery. The PD-PTS replaces these columns with information pertinent to the pathologist, such as the patient's age and gender, anticipated procedure start and stop times, actual start and stop times, and whether a specimen was received. Information displayed on both systems includes patient identifiers, description of procedure, and the procedural status. The PD-PTS also has the capability to list the operating room (OR) schedule from the previous day and up to 5 days in advance, allowing easy access to information regarding past and future procedures. A screen was installed in the grossing room to display ongoing procedures at all times. Since the implementation of the PD-PTS, we have been able to more accurately predict the arrival of specimens and frozen section requests. Time spent contacting the OR to track procedures decreased significantly. Pathologists are also able to direct the transfer of specimen, resulting in timelier transport and the prevention of specimen loss. To our knowledge, this is the first report of a pathology-specific PTS. This system was easily developed through our existing PTS, and resulted in improved patient safety and quality assurance.